How Effective is Plasmonic Enhancement of Colloidal Quantum Dots for Color‐Conversion Light‐Emitting Devices?. Issue 48 (9th November 2017) - Park, Hyun Chul; Isnaeni,; Gong, Suhyun; Cho, Yong‐Hoon
Abstract: Enhancing the fluorescence intensity of colloidal quantum dots (QDs) in case of color‐conversion type QD light‐emitting devices (LEDs) is very significant due to the large loss of QDs and their quantum yields during fabrication processes, such as patterning and spin‐coating, and can therefore improve cost‐effectiveness. Understanding the enhancement process is crucial for the design of metallic nanostructure substrates for enhancing the fluorescence of colloidal QDs. In this work, improved color conversion of colloidal green and red QDs coupled with aluminum (Al) and silver (Ag) nanodisk (ND) arrays designed by in‐depth systematic finite‐difference time domain simulations of excitation, spontaneous emission, and quantum efficiency enhancement is reported. Calculated results of the overall photoluminescence enhancement factor in the substrate of 500 × 500 µm 2 size are 2.37‐fold and 2.82‐fold for Al ND‐green QD and Ag ND‐red QD structures, respectively. Experimental results are in good agreement, showing 2.26‐fold and 2.66‐fold enhancements for Al ND and Ag ND structures. Possible uses of plasmonics in cases such as white LED and total color conversion for possible display applications are discussed. The theoretical treatments and experiments shown in this work are a proof of principle for future studies of plasmonic enhancement of various light‐emitting materials. Abstract : The viability of plasmonic interaction between metal nanodisks and colloidal CdSe‐based quantum dots (green and red) for use in light‐emitting devices is explored, by carrying out in‐depth simulations and analyses to obtain overall photoluminescence enhancement factors. The calculated results are in agreement with the experimental results, allowing one to design plasmonic nanostructures for quantum dot based light‐emitting devices.